Quality characteristics of probiotic yoghurt enriched with honey and by-products left after the production of hemp oil by cold pressing the seeds of Cannabis sativa L. - Gjore Nakov; Biljana Trajkovska; Zlatin Zlatev; Marko Jukić; Jasmina Lukinac (Mljekarstvo)
The purpose of this article is to present possibilities for obtaining a new type of probiotic yoghurt enriched by adding hemp press cake flour (HPCF) in different amounts (2%, 4%, 6%, 8% and 10%). Hemp press cake is a by-product that remains after the cold pressing of industrial hemp (Cannabis sativa L.). The Principal component analysis showed that the amounts of 4 to 10% had a significant effect, and the amount of 2% HPCF had no effect on the physicochemical characteristics of probiotic yoghurt. By the resulting regression model and linear programming algorithm was determined the amount of 4.04% HPCF as the most appropriate in probiotic yoghurt, which was also confirmed in the sensory analysis. The amount of total polyphenols and antioxidant activity significantly increased with the addition of hemp press cake flour from 41.46 mg GAE/mL and 32.2% DPPH inhibition to 111.16 mg GAE/mL to and 55.6% DPPH inhibition in probiotic yoghurt with 10% HPCF.